The Registration Act (XVI of 1908). - Bangladesh; Dhaka Law Reports (Firm) ([Dhaka] : Dhaka Law Reports, 2005)
With upto date amendments and case laws.
Includes index.
Law
Keywords: Bangladesh; Recording and registration -- Bangladesh